Corruption, Composition of Capital Flows, and Currency Crises - Wei, Shang-Jin (World Bank, Washington, DC, 2014)
Crony capitalism and international creditors' self-fulfilling expectations are often suggested as rival explanations for currency crises. A possible link between the two has not been explored. The author shows one channel through which crony capitalism can increase the chance of a currency/financial crisis by altering the composition of capital inflows. Using data on bilateral foreign direct investment and bilateral bank loans, the author finds clear evidence that in corrupt countries the composition of capital inflows is relatively light in foreign direct investment. Earlier studies indicated that a country with a capital inflow structure is more likely to run into a currency crisis down the road (partly through international creditors' self-fulfilling expectations). Therefore, crony capitalism, through its effect on the composition of a country's capital inflows, makes the country more vulnerable to currency crises brought about by self-fulfilling expectations. Corruption may also weaken domestic financial supervision, with a subsequent deterioration in the quality in banks' and firms' balance sheets.